Raising the profile of public health ethics in Australia: time for debate - Craig L. Fry; Anita Peerson; Anne‐Marie Scully (Elsevier, 2004)
Abstract This paper argues for greater dialogue on public health ethics. There has been little discussion in Australia about the significant ethical dilemmas in this field, and there is no agreed framework for analysing and responding to these challenges. We highlight concerns about the suitability of biomedical principles‐based ethics for public health, and encourage public health professionals in this country to reflect on ethical challenges in public health research. A focus on research ethics concerns will deliver concrete examples demonstrating the need for a public health ethics frame work. Recommendations are offered for how public health ethics promotion may occur locally.